The Influence of Leadership Managerial Abilities and Organizational Climate on Personnel Performance in The Identification and Socialization Unit of The Special Detachment 88 Anti-Terrorism Police of The Republic of Indonesia - Nurul Rohim; Zulkifli Rangkuti; Eddy Hermawan Hasudungan Panjaitan (Dinasti Publisher, 2026)
The aim of the research is to describe and analyze the influence of the managerial abilities of leaders which have a significant influence on personnel performance, to find out the influence of organizational climate which has a significant influence on personnel performance and the influence of the managerial abilities of leaders and organizational climate. simultaneously affect performance personnel. The calculated t value for variable X1 (leadership managerial ability) is 6.196 while the t table value for n = 62 is 1.998. So, calculated t > t table or 6.196 > 1.998, it can be concluded that partially the variable Leadership managerial ability has an effect on employee work effectiveness, the calculated t value of variable X2 (organizational climate) is 8.186, while the t table value for n = 62 is 1.998. So the calculated t > t table or 8.186 > 1.998, it is concluded that the organizational climate partially influences the effectiveness of employee work. Thus, H0 is rejected and Ha is accepted, and it is concluded that there is a positive and significant influence between the variable X2 and the variable Y, the calculated F value is 131.225 which is greater than the F table of 2.75 with a significant level of 0.000 because 0.000 < 0.05, it can be said that the variable of the managerial ability of the leader (X1) and the variable of the organizational climate (X2) together influence the performance of personnel (Y).